2020
DOI: 10.4314/ahs.v20i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of gallstone disease in patients undergoing ultrasonography at Mulago hospital, Uganda

Abstract: Background: Gallstone disease (GSD) is the most prevalent medical condition in the pancreatobiliary system. The burden of GSD and its complications are major public health issues globally. It is a common cause of surgical intervention, contributing substantially to health care costs. Most patients are asymptomatic, however 20% become symptomatic after 10 years. Its preva- lence differs among populations and remains unknown in Uganda. Objective: To determine the prevalence and risk factors of GSD in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
6
3
1
Order By: Relevance
“…The achieved results signified a correlation between experience epigastric pain and GSM; the prevalence of gallstones in those who manifested epigastric pain was 45% less than their counterparts without epigastric pain. These data were inconsistent with those of Nimanya et al, where a majority of patients reported epigastric pain 19 . Such data differences concerning epigastric pain may be because the prevalence of dyspepsia and peptic ulcer might have been higher; consequently, non-gallstone epigastric pain was more frequent in the study population.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The achieved results signified a correlation between experience epigastric pain and GSM; the prevalence of gallstones in those who manifested epigastric pain was 45% less than their counterparts without epigastric pain. These data were inconsistent with those of Nimanya et al, where a majority of patients reported epigastric pain 19 . Such data differences concerning epigastric pain may be because the prevalence of dyspepsia and peptic ulcer might have been higher; consequently, non-gallstone epigastric pain was more frequent in the study population.…”
Section: Discussioncontrasting
confidence: 84%
“…Changes in the movement of the gallbladder and sphincter of Oddi lead to biliary stasis in the generation of cholesterol crystals, i.e., reported with iron deficiency (36). We detected no significant relationship between a >10kg weight loss in the last 6 months and developing gallstones 19 , 37 , 38 .…”
Section: Discussioncontrasting
confidence: 61%
“…Gallstone disease remains a global problem, and it is a common indication for surgical intervention. The prevalence of gallstone disease varies widely among different populations, but the prevalence of 5.9% to 21.9% is commonly reported [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A colelitíase é a doença mais prevalente da árvore biliar, responsável pela maior parte das cirurgias eletivas realizadas anualmente 1,2 . É caracterizada principalmente por queixas abdominais e tem como principal tratamento a colecistectomia videolaparoscópica 3,4 , atualmente recomendada precocemente na ausência de contraindicações com o objetivo de prevenir complicações relacionadas à doença e recorrência dos sintomas 5 .…”
Section: Introductionunclassified